중소병원 간호사의 간호전문직관, 학습민첩성, 간호근무환경이 간호업무성과에 미치는 영향 - 김혜영(Kim, Hye-Young); 임수진(Lim, Su-Jin) (근관절건강학회지, 2023)
Purpose: This study attempted to discern the factors that influence nursing professionalism, learning agility, and the nursing practice environment on the performance of nurses. Methods: Data were collected from 202 clinical nurses who both consented to participate and who have worked for more than one year in one of five small- and medium-sized hospitals located in three regions of Korea. The data were analyzed using the SPSS/WIN 26.0 statistical programs. Results: The nurses' performance showed a statistically significant correlation with nursing professionalism (r=.50, p<.001), learning agility (r=.54, p<.001), and nursing practice environment (r=.37, p<.001). Factors affecting the results of nurses' performance in relation to the subjects are those of learning agility (β=.33, p<.001), nursing professionalism (β=.25, p<.001), clinical career (β=.24, p=.001), education level (β=.16, p=.011), and nursing practice environment (β=.15, p=.016). Conclusion: To improve the performance of nurses in medium-sized hospitals, it is necessary to develop a nursing practice environment, programs, and strategies for enhancing nursing professionalism and learning agility.